Encapsulation of the septal cell wall protects Streptococcus pneumoniae from its major peptidoglycan hydrolase and host defenses. - Joana Figueiredo; Mafalda Xavier Henriques; Maria João Catalão; Sara Pinheiro; Ana Rita Narciso; Francisco Mesquita; Bruno Manuel Saraiva; Madalena Carido; Didier Cabanes; Mariana Gomes Pinho; Sérgio Raposo Filipe (PLoS Pathogens, 2022)
Synthesis of the capsular polysaccharide, a major virulence factor for many pathogenic bacteria, is required for bacterial survival within the infected host. In Streptococcus pneumoniae, Wze, an autophosphorylating tyrosine kinase, and Wzd, a membrane protein required for Wze autophosphorylation, co-localize at the division septum and guarantee the presence of capsule at this subcellular location. To determine how bacteria regulate capsule synthesis, we studied pneumococcal proteins that interact with Wzd and Wze using bacterial two hybrid assays and fluorescence microscopy. We found that Wzd interacts with Wzg, the putative ligase that attaches capsule to the bacterial cell wall, and recruits it to the septal area. This interaction required residue V56 of Wzd and both the transmembrane regions and DNA-PPF domain of Wzg. When compared to the wild type, Wzd null pneumococci lack capsule at midcell, bind the peptidoglycan hydrolase LytA better and are more susceptible to LytA-induced lysis, and are less virulent in a zebrafish embryo infection model. In this manuscript, we propose that the Wzd/Wze pair guarantees full encapsulation of pneumococcal bacteria by recruiting Wzg to the division septum, ensuring that capsule attachment is coordinated with peptidoglycan synthesis. Impairing the encapsulation process, at localized subcellular sites, may facilitate elimination of bacteria by strategies that target the pneumococcal peptidoglycan.